2020
DOI: 10.1186/s12885-020-07363-6
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of LNM risk factors and the effect of chemotherapy in early colorectal cancer: A Chinese multicenter study

Abstract: Background Estimating the risk of lymph node metastasis (LNM) is crucial for determining subsequent treatments following curative resection of early colorectal cancer (ECC). This multicenter study analyzed the risk factors of LNM and the effectiveness of postoperative chemotherapy in patients with ECC. Methods We retrospectively analyzed the data of 473 patients with ECC who underwent general surgery in five hospitals between January 2007 and October 2018. The correlations between LNM and sex, age, tumor siz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 35 publications
(30 reference statements)
1
9
0
Order By: Relevance
“…The present study showed that the incidence of LNM among these patients with T1 or T2 cancer was 11.4% (8% in T1 and 16.2% in T2), which is consistent with the rates of 12.7% to 21% reported in previous studies (4.7-17.6% for T1 and 18.0-24.5% for T2) [1,2,7,9,[13][14][15]. LNM is well known as an important risk factor for CRC and is hence included in the assessment of tumor stage [25].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study showed that the incidence of LNM among these patients with T1 or T2 cancer was 11.4% (8% in T1 and 16.2% in T2), which is consistent with the rates of 12.7% to 21% reported in previous studies (4.7-17.6% for T1 and 18.0-24.5% for T2) [1,2,7,9,[13][14][15]. LNM is well known as an important risk factor for CRC and is hence included in the assessment of tumor stage [25].…”
Section: Discussionsupporting
confidence: 92%
“…Many previous studies have investigated tumor location as a predictive factor for LNM. Some studies reported a higher rate of LNM for cancers located in the rectum than those located in the colon [9,11], whereas others did not find an association between tumor location and metastasis [4][5][6]8,10,14]. One possible reason for these discrepancies is that some studies divided the tumor location into three, five, or eight categories [5,6,10,14] instead of two categories (colon and rectum).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 However, the association between depth of invasion and LN metastasis is not as clear as expected, and depth of invasion has low predictive value for LN metastasis. For example, in a study of 473 patients with early colorectal cancer in China from 2007 to 2018, larger tumor size and the presence of lymphovascular invasion were associated with higher risk of LN metastasis; 37 no difference in LN metastasis was observed based on depth of invasion. 37 All guidelines in the last 5 years refer to >1000 μm as an unfavorable risk factor for LN metastasis.…”
Section: Lymph Node Metastasis and Submucosal Invasionmentioning
confidence: 99%
“…For example, in a study of 473 patients with early colorectal cancer in China from 2007 to 2018, larger tumor size and the presence of lymphovascular invasion were associated with higher risk of LN metastasis; 37 no difference in LN metastasis was observed based on depth of invasion. 37 All guidelines in the last 5 years refer to >1000 μm as an unfavorable risk factor for LN metastasis. Despite the general acceptability of 1000 μm as the predictive cut off, the depth of invasion associated with LN metastasis varied in the 39 As mentioned earlier, the risk of LN metastasis increases in proportion to the depth of submucosal invasion as determined by Haggitt and Kudo classification methods.…”
Section: Lymph Node Metastasis and Submucosal Invasionmentioning
confidence: 99%